2008
DOI: 10.1111/j.1525-1438.2007.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of debulking surgery in advanced ovarian cancer

Abstract: It is clear that primary debulking remains the standard of care within the treatment of advanced ovarian cancer (FIGO stage III and IV). This debulking surgery should be performed by a gynecological oncologist without any residual tumor load, or so-called "optimal debulking." Over the last decades, interest in the use of neoadjuvant chemotherapy together with an interval debulking has increased. Neoadjuvant therapy can be used for patients who are primarily suboptimally debulked due to an extensive tumor load.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 74 publications
(98 reference statements)
0
52
0
1
Order By: Relevance
“…These studies have been extensively reviewed and due to their retrospective nature, the results are, fraught with biases including variable patient selection and lack of wellmatched control groups [48][49][50][52][53][54]. In many studies, patients selected to undergo NACT were older, had a greater tumor burden, higher stage and grade of disease, a poorer performance status, and had other medical co-morbidities precluding them from undergoing aggressive cytoreductive surgery compared to control groups.…”
Section: Current Datamentioning
confidence: 98%
“…These studies have been extensively reviewed and due to their retrospective nature, the results are, fraught with biases including variable patient selection and lack of wellmatched control groups [48][49][50][52][53][54]. In many studies, patients selected to undergo NACT were older, had a greater tumor burden, higher stage and grade of disease, a poorer performance status, and had other medical co-morbidities precluding them from undergoing aggressive cytoreductive surgery compared to control groups.…”
Section: Current Datamentioning
confidence: 98%
“…19,20 In situations where the ability to achieve an optimal cytoreduction is unlikely, neoadjuvant chemotherapy followed by interval cytoreduction may be appropriate. 3 Thus, laparoscopy offers a less morbid approach for determining which patients will likely have suboptimal cytoreduction at the time of primary surgery and hence benefit from neoadjuvant chemotherapy. Vergote et al 21 reported a series of 285 patients who underwent open laparoscopy to determine whether optimal debulking is possible.…”
Section: Discussionmentioning
confidence: 99%
“…2 In patients with disease thought not to be optimally resectable, the use of neoadjuvant chemotherapy to reduce tumor load can allow for interval surgical debulking. 3 Advances in laparoscopic surgery have extended this minimally invasive surgical approach to managing ovarian cancer. In early stage ovarian cancer, multiple studies have demonstrated feasibility and efficacy of complete laparoscopic staging.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the well known evidence in early stage ovarian cancer patients, we are aware of no data on the role of secondary MDS in patients with advanced stage disease or prognostic factors for these patients [3][4][5][6][7][8][9][10]. Two previous studies, EORTC/GCCG-55865 and GOG-152 had analyzed the role of re-surgery in these advanced staged patients [11,12].…”
Section: Introductionmentioning
confidence: 96%